(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
The formulation of this research problem is how the responsibility of the drop shipper in E-Commerce transactions in terms of Law Number 8 of 1999 concerning consumer protection and legal relations between parties in E-Commerce transactions by way of dropshipping. This study aims to determine and analyze the responsibility of the drop shipper in e-commerce transactions and legal relations between parties in e-commerce transactions by means of dropshipping. This thesis research uses a type of normative legal research, which is based on statutory regulations that use primary legal materials that have binding power as the main basis for this research, including the Civil Code and other related regulations. Secondary materials, namely materials that are closely related to primary legal materials and help analyze and understand primary legal materials, such as the results of previous research related to the Law of Consumer Protection. The results of this study indicate that the responsibility of the drop shipper as a business actor bears full responsibility for all legal consequences of the agreement. Then related to the legal relationship between the dropshipper and the consumer, it is a legal relationship between the seller and the buyer which creates rights and obligations between the two of them and leads to the legal consequences that occur. Abstrak: Rumusan masalah penelitian ini bagaimanakah tanggung jawab dropshipper dalam transaksi E-Commerce ditinjau dari Undang-undang Nomor 8 Tahun 1999 tentang perlindungan konsumen dan hubungan hukum antara pihak dalam transaksi E-Commerce dengan cara dropship. Penelitian ini bertujuan untuk mengetahui dan menganalisis Tanggung Jawab Dropshipper dalam Transaksi E Commerce dan Hubungan Hukum antara pihak dalam transaksi e-commerce dengan cara dropship. Penelitian skripsi ini menggunakan tipe penelitian hukum normatif, yang disandarkan pada peraturan Perundang-undangan yang menggunakan bahan hukum primer yang mempunyai kekuatan mengikat sebagai landasan utama dalam penelitian ini, diantaranya KUHPerdata dan peraturan terkait lainnya. Bahan sekunder, yaitu bahan-bahan yang erat hubungannya dengan bahan hukum primer dan membantu menganilisis dan memahami bahan hukum primer, seperti hasil penelitian sebelumnya yang berkaitan dengan Hukum Perlindungan Konsumen. Hasil penelitian ini menunjukkan bahwa Tanggung Jawab Dropshipper sebagai pelaku usaha memikul tanggung jawab secara penuh, terhadap segala akibat hukum dari perjanjian. Kemudian terkait Hubungan hukum antara Dropshipper dan konsumen merupakan hubungan hukum antara penjual dan pembeli yang menimbulkan hak dan kewajiban antara keduanya serta bermuara pada adanya akibat hukum yang terjadi.